DOWRY FUNCTION IN PERSPECTIVE OF MUBADALAH - Zulaikha, Siti; Nurjanah, Siti; Faizin, Mu'adil; Ferliandi, Agus Salim (Universitas Islam Negeri Raden Intan Lampung, 2022)
Dowry is a gift from a husband to his wife which is done at the time of the marriage contract. Dowry is something that is not included in the conditions and pillars of marriage, but it must exist. Meanwhile, mubadalah is an approach used to understand the verses in the Qur'an which are general in form but at first glance, they seem to be biased towards one gender, or specifically for men where women are not addressed, and specifically women and men have not been addressed. so that the main message of the text can then be applied to the two sexes. This paper aims to examine the function of dowry using a young perspective which will use the literature study method, with data sources from all literature discussing dowry and mubadalah. The analysis will be carried out using qualitative methods with deductive thinking. In the discussion, it is known that dowry in the perspective of mubadalah is a provision that is set to strengthen the position of women. So it can be concluded that the dowry is actually to uphold the honor of women, so that the higher the appropriateness of the dowry given voluntarily, it can be considered as an indicator that the husband is committed and can prove his promise of sincerity. Keywords: Dowry, Mubadalah, Level of Appropriateness